Recent Technological Developments in the Diagnosis and Treatment of Cerebral Edema. Issue 11 (16th August 2021) - Deshmukh, Karthikeya P.; Rahmani Dabbagh, Sajjad; Jiang, Nan; Tasoglu, Savas; Yetisen, Ali K.
Abstract : Latest technological advancements in neurocritical care have translated to improved clinical outcomes and have paved the way for the effective diagnosis and treatment of cerebral edema. Effective management of cerebral edema has the potential to provide a personalized treatment by obtaining the complete pathophysiological information of the patient. The aims of this review are to inform the reader about the research and development in this field in the past decade as well as the materialization of scientific literature through patents. There is a growing interest in multimodal monitoring of the diseased brain as it provides a necessary means to implement effective intervention strategies. Although there is a gradual shift toward the adoption of noninvasive devices for research purposes, their clinical applications are hindered by their inaccuracies. However, the inherent risk of complication and high costs of implementation challenge the status quo. The role of neuroprotectants is explored and the combination of neurodiagnostic and neuroprotective approaches is proposed. Finally, the impacts of the current state of global affairs are discussed and it is predicted that the rising number of traumatic brain injury patents will inevitably translate to improvements in technologies to effectively address cerebral edema. Abstract : Herein, the recent technological developments in the diagnosis and treatment of cerebral edema are reviewed to inform the reader about the current diagnostic tools available on the market, the cutting edge technology in the form of patents, and offer a preview of the technologies in the research phase that are set to dominate the scene of future neurodiagnostic technology.